2020
DOI: 10.1111/ajt.15577
|View full text |Cite
|
Sign up to set email alerts
|

Myosteatosis to predict inferior perioperative outcome in patients undergoing orthotopic liver transplantation

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Abbreviations: AASLD American Association for the Study of Liver Diseases AUC area under the curve AUROC area under the receiver operating characteristics curve BAR balance of risk BC body composition BMI body mass index CCI compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(142 citation statements)
references
References 44 publications
4
134
0
4
Order By: Relevance
“…Our data are in line with previous studies demonstrating an association of sarcopenia and an impaired prognosis in patients with nonalcoholic liver disease ( 18 ), liver cirrhosis ( 19 ), cardiovascular ( 20 ), and lung diseases ( 21 ). Furthermore, it was demonstrated that sarcopenia might predict outcome of patients undergoing therapeutic interventions such as transcatheter arterial chemoembolization (TACE) ( 22 ), liver transplantation ( 23 ), or colorectal cancer surgery ( 24 ). Within our study, we not only analyzed the association between sarcopenia and patient’s outcome but also of myosteatosis and patients´ outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in line with previous studies demonstrating an association of sarcopenia and an impaired prognosis in patients with nonalcoholic liver disease ( 18 ), liver cirrhosis ( 19 ), cardiovascular ( 20 ), and lung diseases ( 21 ). Furthermore, it was demonstrated that sarcopenia might predict outcome of patients undergoing therapeutic interventions such as transcatheter arterial chemoembolization (TACE) ( 22 ), liver transplantation ( 23 ), or colorectal cancer surgery ( 24 ). Within our study, we not only analyzed the association between sarcopenia and patient’s outcome but also of myosteatosis and patients´ outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] In addition, skeletal muscle radiation attenuation (SM-RA) has emerged as a radiological marker indicative of myosteatosis, which has been shown to be predictive of poor outcome following oncological surgery. 2,10,11,48 Myosteatosis is characterized by increased interand intra-myocellular fat stores, which can be influenced by dietary pattern and activity changes. This is related to reduced physical fitness and reduced muscle function.…”
Section: Introductionmentioning
confidence: 99%
“…Besides general loss of muscle mass, the loss of muscle function is often associated with increased proportions of inter-and intramuscular fat, which is called myosteatosis and represents a subelement of sarcopenia [14]. Myosteatosis has been identified as another important parameter and has also been linked to adverse outcomes in a variety of different diseases such as, e.g., liver cirrhosis and patients undergoing liver surgery [15][16][17].…”
Section: Introductionmentioning
confidence: 99%